Microbial imbalance in Darier disease: Dominance of various staphylococcal species and absence of Cutibacteria - Dóra Plázár; Zseraldin Metyovinyi; Norbert Kiss; András Bánvölgyi; Nóra Makra; Zsuzsanna Dunai; Balázs Mayer; Péter Holló; Márta Medvecz; Eszter Ostorházi (Scientific Reports)
Abstract Darier disease (DD) is a rare autosomal dominant genodermatosis characterized by erythematous papules and plaques mainly involving sebaceous areas, such as the face, chest and back. Skin microbiome plays an essential role in maintaining skin homeostasis. A disturbed skin microbiome may contribute to the exacerbation of DD. We investigated the bacterial composition of two predilectional sites in DD patients and healthy individuals. We also measured the microbiome composition of deeper skin layers, where diversity was significantly reduced compared to the superficial layer of the skin from the same area. The microbiome of DD patients at lesional sites differed from that of non-lesional skin areas; moreover, non-lesional sites were different from those of the controls. Lesional areas were dominated by Staphylococcus species, such as S. aureus, S. epidermidis, S. hominis, S. sciuri, and S. equorum. However, levels of Cutibacterium acnes (formerly Propionibacterium acnes) and C. acnes subspecies defendens were significantly lower in lesional sites than in non-lesional sites. A significant decrease was measured in the levels of these two bacteria between non-lesional and control samples. Our findings may indicate that alterations in the skin microbiome could contribute to the inflammation of skin lesions in DD.